2018
DOI: 10.5152/turkpediatriars.2017.5143
|View full text |Cite
|
Sign up to set email alerts
|

The effect of phototherapy on sister chromatid exchange with different light density in newborn hyperbilirubinemia

Abstract: Aim: Concerns of possible genotoxic effects of hyperbilirubinemia and phototherapy were raised from experimental and observational studies in neonates. The purpose of this study was to assess the effect of hyperbilirubinemia and phototherapy with three different methods on DNA damage by investigating sister chromatid exchange frequency. Material and Methods: Patients whose gestational ages were >37 weeks and bilirubin levels above phototherapy limits were enrolled into three groups and each group was planned t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…It has also been suggested that neonatal phototherapy may increase the risk of hemangioma in infants, which may be associated with oxidative stress caused by phototherapy, which can damage vascular endothelial cells and stimulate the formation of new blood vessels ( 111 ). The increased risk of cancer in children treated with phototherapy may be associated with hyperbilirubinemia per se , phototherapy or a combination of the two ( 112 ).…”
Section: Adverse Reactions Of Phototherapy For Neonatal Hyperbilirmentioning
confidence: 99%
“…It has also been suggested that neonatal phototherapy may increase the risk of hemangioma in infants, which may be associated with oxidative stress caused by phototherapy, which can damage vascular endothelial cells and stimulate the formation of new blood vessels ( 111 ). The increased risk of cancer in children treated with phototherapy may be associated with hyperbilirubinemia per se , phototherapy or a combination of the two ( 112 ).…”
Section: Adverse Reactions Of Phototherapy For Neonatal Hyperbilirmentioning
confidence: 99%
“…Subsequently, it is reabsorbed by OATP1B1 and OATP1B3 proteins in hepatocytes. Because OATP1B1 and OATP1B3 proteins are abnormal in RS, bilirubin reuptake and excretion by the liver is less efficient, and this causes accumulation of bilirubin in the blood and urine; this is reflected in the phenotype as jaundice and dark colored urine ( 4 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, light is used in modern medicine in the treatment of many diseases [42][43][44]. According to a study by Tuzun and Cesare different color fluorescences can be obtained when examining various diseases with a Wood light (black light), which is a fluorescent lamp that emits a purple light.…”
Section: The Effect Of the Rays And Colors Of External Factors On Thementioning
confidence: 99%